The development of the "Water Campaign": Combining social marketing and intervention mapping. Issue 4 (10th October 2016) - Blanchette, Lyne M.G.; van de Gaar, Vivian M.; Raat, Hein; French, Jeff; Jansen, Wilma
Abstract : Purpose: This paper aims to present a description of the development and implementation of a combined school- and community-based intervention for the prevention of overweight among children, using the combined methods of social marketing (SMk) and intervention mapping (IM). Design/methodology/approach: The SMk total process planning (TPP) framework was used, a simple but robust framework that consists of five stages: scoping, development, implementation, evaluation and follow-up. In addition, IM tools were embedded in the development stage to strengthen the development element of the campaign. Findings: The use of the SMk TPP framework led to the selection of one specific target segment and behaviour. IM tools helped to select the most important and modifiable determinants and behaviours in the target segment, as well as to select and appropriately apply theoretical methods for influencing determinant and behaviour change. The resulting "Water Campaign" was aimed at Turkish and Moroccan mothers and their 6-12-year-old-children (target segment). This intervention addresses the consumption of sugar-sweetened beverages through the promotion of tap water drinking (target behaviour). The systematic involvement of key stakeholders resulted in capacity-building and co-creation. Originality/value: A key finding of the present work is that the SMk TPP framework and IM tools can be successfully combined in intervention development, helping to develop enhanced interventions. Combining these methods led to a theory-based and client-oriented intervention, which was directed at multiple ecological levels and which systematically involved key stakeholders. With this detailed description of the intervention development, this paper aims to assist other researchers and practitioners in their quest to develop better interventions.